An investigation of absenteeism amongst blue-collar workers: a mixed methods approach - Kroon, Kim (Rhodes University, Faculty of Commerce, Rhodes Business School, 2016)
Absenteeism affects organisations in many different ways, therefore it is essential to investigate absenteeism with the aim of minimising absence levels. The focus of the research was to investigate absenteeism amongst blue-collar workers at a Global Logistics Supplier. The objectives of this research were to identify the main types of absenteeism, to compare the views of blue-collar workers and management on the causes attributed to absenteeism, to describe how absenteeism has been measured and managed, and to make recommendations to the company on ways to minimize absenteeism based on the findings. Quantitative data in the form of monthly absenteeism statistics relating to each leave type, was examined for trends relating to absenteeism levels amongst blue-collar workers at the company. Semi-structured interviews were then carried out with management and blue-collar workers to examine the causes of absenteeism and its management. The results showed that there was a discrepancy between the views of management and blue-collar workers at the company on the perceived causes of absenteeism. On the other hand, both management and the blue-collar workers identified Monday and Friday as the most prevalent days on which employees are absent from the workplace. This finding suggests that more research should be conducted on this trend in blue-collar workers. In exploring how absenteeism is dealt with, management within the company stated that discipline was the most effective way of keeping absenteeism levels low amongst employees. The limitations and delimitations of the research were recognised and further research ideas were given. It was also recommended that managers and supervisors address the workplace issues and identify when a worker's performance and interpersonal relationships are strained in order to effectively minimise absenteeism. It is also recommended they implement a wellness programme.
Keywords: Uncatalogued